THE THEORY OF MANUFACTURING COSTS. - Fess, Philip E. (The Accounting Review, 1961)
The proper treatment of manufacturing costs has been a topic of discussion among accountants for many decades. Various treatments recommended range from including only prime costs in inventory to a full costing policy. In recent years, a new treatment of manufacturing costs has been introduced into accounting literature. The advocates of this new concept, generally referred to as direct costing, and the supporters of the conventional costing concept have been engaged in a lively debate as to the relative merits of these concepts. Such debate is desirable and necessary since every new concept should stand the test of controversy before being accepted or rejected by the accounting profession. Most of the debate thus far has centered around the practical usefulness of the two concepts. It is difficult to find a thorough treatment of the theory of manufacturing costs. The fundamental difference between direct costing and absorption costing is in the treatment of fixed manufacturing costs; both costing concepts treat the variable manufacturing costs as part of the product cost. Absorption costing charges fixed manufacturing costs to the product while direct costing charges these fixed manufacturing costs to the period in which incurred.